DNA Damage in CD133-Positive Cells in Barrett's Esophagus and Esophageal Adenocarcinoma - Raynoo Thanan; Ning Ma; Yusuke Hiraku; Katsunori Iijima; Tomoyuki Koike; Tooru Shimosegawa; Mariko Murata; Shosuke Kawanishi (Hindawi Limited, 2016)
Barrett's esophagus (BE) caused by gastroesophageal reflux is a major risk factor of Barrett's esophageal adenocarcinoma (BEA), an inflammation-related cancer. Chronic inflammation and following tissue damage may activate progenitor cells under reactive oxygen/nitrogen species-rich environment. We previously reported the formation of oxidative/nitrative stress-mediated mutagenic DNA lesions, 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) and 8-nitroguanine, in columnar epithelial cells of BE tissues and cancer cells of BEA tissues. We investigated the mechanisms of BEA development in relation to oxidative/nitrative DNA damage and stem cell hypothesis. We examined 8-nitroguanine and 8-oxodG formation and the expression of stem cell marker (CD133) in biopsy specimens of patients with BE and BEA by immunohistochemical analysis in comparison with those of normal subjects. CD133 was detected at apical surface of columnar epithelial cells of BE and BEA tissues, and the cytoplasm and cell membrane of cancer cells in BEA tissues. DNA lesions and CD133 were colocalized in columnar epithelial cells and cancer cells. Their relative staining intensities in these tissues were significantly higher than those in normal subjects. Our results suggest that BE columnar epithelial cells with CD133 expression in apical surface undergo inflammation-mediated DNA damage, and mutated cells acquire the property of cancer stem cells with cytoplasmic CD133 expression.